Accessibility of Cypriot University websites in Cyprus - Mavrou, Katerina; Zaphiris, Panayiotis; Michailidou, Eleni (My University, 2011)
Abstract: Access and equity in higher education is a complicated discipline related to social, economical, technological and political developments in a country. This paper is a work in progress and it aims to discuss issues of accessibility in Higher education regarding equal opportunities in the use of technology for students with disabilities. Accessibility to technology and with technology, especially in the internet era, includes different types of physical and digital design. These not only refer to specialised interface devices often referred to as assistive technology, but also to the accessibility of the web itself (Zaphiris & Zacharia, 2001). Examining access in higher education from the point of view of technology, this paper aims to: 1. briefly present and discuss the provisions of the current Cyprus and European legislation regarding the use of accessible technology and access to technology (and the use of the web) in higher education for students with disabilities. 2. investigate the ways universities respond to the needs of their students with disabilities regarding the use of accessible technology and access to technology 3. analyze the accessibility of the Cyprus universities’ web sites Data collection involves: (a) analysis of Cyprus and European documentation, (b) interviews with officers of the student affairs and welfare departments of each university and (c) expert accessibility evaluation of the websites of all universities in Cyprus. The educational system in Cyprus is highly centralised and policies of funding, administration and pedagogy are centrally developed by the government (Symeonidou, 2002). Education is compulsory until the age of 15, and almost 100% of the students continue their education in the lyceum or technical school, and the majority continue in further and higher education, in Cyprus and abroad. With the establishment of 3 public and 4 private universities in the country the numbers of student continuing in higher education are highly increase in the last 4 years, including an important number of students with disabilities. Provision for the education of students with disabilities is traditionally called by the 1999 Education Act for the Education of Children with Special Needs (MOEC, 1999), which was formally implemented in 2001. Preliminary data and information from previous studies evidenced that among others, the legislation is covering general issues of accessibility (cognitive, physical and communication), which also may imply technology, without though providing any specific guidelines (Mavrou, 2011). In addition, it provides relevant directions for higher education, but mainly poses the responsibility to the higher educational institutions. Hence, issues of accessibility and technology do not seem to be officially directed by legislation or regulations and guidelines by the Cyprus government, at any level of education or other sectors, even if the country have signed relevant EU conventions and documentation. Accessibility for information on the Web has been well regulated in the United States (U.S.) and the European Commission (DRC, 2004; Section508, 2011). The European approach to ensuring the availability of accessible information on public Web sites is encapsulated in the eEurope Action Plan 2002 which emphasises that, “Public sector web sites […] must be designed to be accessible to ensure that citizens with disabilities can access information and take full advantage of the potential for e-government” (EU Commission, 2000). Unfortunately the Cypriot legislature is not yet in line with the European action plan on the issue of web accessibility. There are no specific legislative or regulatory measures regarding eAccessibility for public or private websites in Cyprus (eInclusion). However, Article 16 of the new EU Structural Funds regulations is expected to have an impact on eAccessibility and as Cyprus has signed the Convention, now Article 9 sets forth the obligation of the country to ensure accessibility to the Internet (but it is not a legislation). As per eInclusion in Cyprus, it was planned that within 2010, these sites would be further enhanced based on WCAG 2.0, level AA (EU. 2010). To our knowledge, only one previous study has analyzed Cypriot web sites with respect to accessibility via automated testing on WCAG1.0 (Zaphiris & Zacharia, 2001). The results showed that the Cyprus websites, including academic websites, were ranked very low in terms of accessibility (only 20% of them were Bobby approved). The present study, aims to investigate the accessibility of new technologies, especially the web, of universities, 10 years after the first study, as well as after Cyprus joined the EU where signed relevant conventions and documents.